Rapid Development and Characterization of Chromosome Specific Translocation Line of Thinopyrum elongatum with Improved Dough Strength - Kumar, Aman; Garg, Monika; Kaur, Navneet; Chunduri, Venkatesh; Sharma, Saloni; Misser, Swati; Kumar, Ashish; Tsujimoto, Hisashi; Dou, Quan-Wen; Gupta, Raj K. (Frontiers in Plant Science, 2017)
The protein content and its type are principal factors affecting wheat (Triticum aestivum) end product quality. Among the wheat proteins, glutenin proteins, especially, high molecular weight glutenin subunits (HMW-GS) are major determinants of processing quality. Wheat and its primary gene pool have limited variation in terms of HMW-GS alleles. Wild relatives of wheat are an important source of genetic variation. For improvement of wheat processing quality its wild relative Thinopyrum elongatum with significant potential was utilized. An attempt was made to replace Th. elongatum chromosome long arm (1EL) carrying HMW-GS genes related to high dough strength with chromosome 1AL of wheat with least or negative effect on dough strength while retaining the chromosomes 1DL and 1BL with a positive effect on bread making quality. To create chromosome specific translocation line [1EL(1AS)], double monosomic of chromosomes 1E and 1A were created and further crossed with different cultivars and homoeologous pairing suppressor mutant line PhI. The primary selection was based upon glutenin and gliadin protein profiles, followed by sequential genomic in situ hybridisation (GISH) and fluorescent in situ hybridization (FISH). These steps significantly reduced time, efforts and economic cost in the generation of translocation line. In order to assess the effect of translocation on wheat quality, background recovery was carried out by backcrossing with recurrent parent for several generations and then selfing while selecting in each generation. Good recovery of parent background indicated the development of almost near isogenic line (NIL). Morphologically also translocation line was similar to recipient cultivar N61 that was further confirmed by seed storage protein profiles, RP-HPLC and scanning electron microscopy. The processing quality characteristics of translocation line (BC4F6) indicated significant improvement in the gluten performance index, dough mixing properties, dough strength and extensibility. Our work aims to address the challenge of limited genetic diversity especially at chromosome 1A HMW-GS locus. We report successful development of chromosome 1A specific translocation line of Th. elongatum in wheat with improved dough strength.